2013
DOI: 10.1007/s10103-013-1391-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different mechanical and chemical surface treatments on the repaired bond strength of an indirect composite resin

Abstract: This study compared the effects of two mechanical surface preparation techniques, air abrasion and Nd:YAG laser, with the use of two adhesive systems, self-etch and etch and rinse, on the repair bond strengths of an indirect composite resin. One hundred fifty cylindrical samples of an indirect composite resin were prepared and randomly divided into six groups (n = 25). In groups 1-3, the composite resin surfaces were respectively prepared as follows: no roughening, roughening by air abrasion, and roughening by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
30
0
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 17 publications
3
30
0
4
Order By: Relevance
“…SEM and AFM images in the present study confirmed this. Previous studies (9,12,21) have shown that roughening the surface with air abrasion results in an increase in the repair bond strength of composite resins. Contrary to the results of the present study, Alizadeh et al (10) reported that use of air abrasion did not result in an increase in the repair bond strength of silorane-based composite resin.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…SEM and AFM images in the present study confirmed this. Previous studies (9,12,21) have shown that roughening the surface with air abrasion results in an increase in the repair bond strength of composite resins. Contrary to the results of the present study, Alizadeh et al (10) reported that use of air abrasion did not result in an increase in the repair bond strength of silorane-based composite resin.…”
Section: Discussionmentioning
confidence: 95%
“…Since giomer is a biphasic material, consisting of a resin matrix and filler particles, it is possible to believe that the mechanism of the effect of laser on composite resins holds true in the case of giomer, too. In this context, previous studies have shown that surface roughening with Nd:YAG laser results in an increase in repair bond strength of indirect (12) and silorane-based composite resins (8). However, in a study by Akyil et al , use of Nd:YAG laser alone did not result in an increase in repair bond strength of feldspathic ceramic (19).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The findings of the current study demonstrate the importance of sandblasting and micromechanical retention in the bis-acryl temporary resin repair. Some studies have also shown that micromechanical retention is the most significant factor in the filling composite resin repair [5,16,17]. However, some investigations have reported the reduced repair bond strength after sandblasting in the filling composite resin repair [18][19][20].…”
Section: Discussionmentioning
confidence: 99%